WHY WE DO (NOT) SORT? QUALITATIVE ANALYSIS OF THE DETERMINANTS OF HOUSEHOLD WASTE RECYCLING BEHAVIOUR - Budraitė, Ieva (Politologija, 2015)
A considerable empirical literature has arisen to explain what determines people’s decision to participate in such a pro-environmental behavior as recycling. Summarizing it, explanatory factors could be grouped into three main drivers: an effective and user-friendly infrastructure, information available to the residents, and their values and motivation. Examining the studies carried out in the context of Lithuania, it could be seen that the first two factors are given much attention, while the deep and extensive research of the third one is missing, regardless of how problematic the recycling issue in the country is. For this reason, the aim of the article is to identify the valuable and motivational drivers that influence the Lithuanian population sorting behavior and could help in formulating recommendations for effective interventions to promote or change it. Residents of the Alytus city municipality – population of the most advanced region in the field of waste management – are chosen as the sample of research. The Theory of Planned Behavior provides the tools and analysis model for the research. The qualitative methodological approach and a semi-structured interview as a method are used. The survey was conducted in March and April 2014, using a convenience sampling of 32 people. Content analysis using the Nvivo.10 QSR software package was applied for the data research. On the basis of findings, four prevailing behavioral models were distinguished: (1) “I do sort!” – active and conscious, (2) “I do as needed” – passive but acting, (3) “I will not do!” – frustrated and opposing, (3) “I do not care...” – unthinking and dormant. All of them are determined by the different conjuncture of the factors identified, therefore, organizing interventions to promote household waste sorting, the measures taken should be selected based on the characteristics of each type of behavior.